Efficacy of Cathelicidin LL-37 in an MRSA Wound Infection Mouse Model - Oriana Simonetti; Oscar Cirioni; Gaia Goteri; Guendalina Lucarini; Elżbieta Kamysz; Wojciech Kamysz; Fiorenza Orlando; Giulio Rizzetto; Elisa Molinelli; Gianluca Morroni; Roberto Ghiselli; Mauro Provinciali; et al. (MDPI AG, 2021)
Background: LL-37 is the only human antimicrobial peptide that belongs to the cathelicidins. The aim of the study was to evaluate the efficacy of LL-37 in the management of MRSA-infected surgical wounds in mice. Methods: A wound on the back of adult male BALB/c mice was made and inoculated with Staphylococcus aureus. Two control groups were formed (uninfected and not treated, C0; infected and not treated, C1) and six contaminated groups were treated, respectively, with: teicoplanin, LL-37, given topically and /or systemically. Histological examination of VEGF expression and micro-vessel density, and bacterial cultures of wound tissues, were performed. Results: Histological examination of wounds in the group treated with topical and intraperitoneal LL-37 showed increased re-epithelialization, formation of the granulation tissue, collagen organization, and angiogenesis. Conclusions: Based on the mode of action, LL-37 has a potential future role in the management of infected wounds.